Gas6 as a predictor of esophageal varices in patients affected by hepatitis C virus related-chronic liver disease. (January 2018) - Bellan, Mattia; Sainaghi, Pier Paolo; Minh, Margherita Tran; Minisini, Rosalba; Molinari, Luca; Baldrighi, Marco; Salmi, Livia; Barbaglia, Matteo Nazzareno; Castello, Luigi Mario; Ravanini, Paolo; Avanzi, Gian Carlo; Pirisi, Mario
Aim: Plasma Gas6 was tested as an alternative to Baveno VI criteria (liver stiffness <20 kPa and platelet count >150 × 10 9 /l) in an endoscopy-sparing strategy.Methods: A total of 160 patients with chronic hepatitis C and advanced fibrosis/cirrhosis underwent, on the same occasion, liver elastography, upper endoscopy, a platelet count and serum Gas6 measurement.Results: A total of 74/160 (46%) patients had esophageal varices, that were small (diameter <5 mm) in 57/160 (34%) and large in 17/160 (11%) cases. A total of 34/160 (21%) patients satisfied Baveno VI criteria, according to which screening for esophageal varices could have been omitted; 1/34 had large varices (sensitivity 94%). A plasma Gas6 value <45 ng/ml, detected in 34/160 (21%) patients, was also 94% sensitive.Conclusion: Plasma Gas6 might represent a feasible alternative to Baveno VI criteria when transient elastography is unavailable/unsuccessful.